Phased array high intensity focused ultrasound - Chen, Siyu (2016)
Abstract The final year project is to simulate HIFU transducers with different geometries and number of elements using MATLAB. MATLAB generate the pressure distribution and temperature distribution figures. By analysis the pressure distribution and temperature figures, we can design or choose the suitable high intensity focused ultrasound phased arrays to treat prostate cancer, kidney stone and other diseases. A comparison of the properties (pressure distribution temperature distribution) around the focus spot between the different transducers. According the results to find best transducer for clinical use in non-invasive treatment method. Cylindrical transducers have smaller beam size over single concave transducer, but the peak pressure of both transducer are more or less same. Cylindrical transducers have different number of elements have same beam size and peak pressure. Annular transducers with multi elements have large focal spot than cylindrical transducers and maximum pressure are equal. When focus point away from center, the peak pressure of annular transducer will increase, but the peak pressure of cylindrical transducer will decrease. With larger frequency of transducers, the lesser of peak pressure in cylindrical transducer. The finding obtained from MATLAB simulation indicate cylindrical transducer has better performance in treating non-invasive diseases. Because cylindrical transducer has smaller beam which means lesser tissue will be affected. Second acoustic intensity around cylindrical transducer is much lower than other geometries shape transducer so that ultrasound have lesser chance to damaging intervening tissue. Last but not least, when shift away focus point, the maximum pressure will increase. With greater peak pressure, treatment of cancer will be more effective.